Elucidating the Effect of Temperature Stress on the Protein Content, Total Antioxidant Capacity, and Antioxidant Enzyme Activities in Tetranychus urticae (Acari: Tetranychidae) - Peng-Cheng Nie; Ruo-Lan Yang; Jing-Jiang Zhou; Youssef Dewer; Su-Qin Shang (Insects, 2023)
Tetranychus urticae Koch is a worldwide agricultural pest mite that feeds on more than 1100 kinds of crops. The mite has developed a high level of tolerance to high temperatures, but the physiological mechanism underlying the outstanding adaptability of this pest to high temperatures remains unclear. To clarify the physiological mechanisms of T. urticae in response to short-term heat stress, four temperatures (36, 39, 42, and 45 °C) and three short-term heat durations (2, 4, and 6 h) were conducted to test the effects on protein content, the activities of superoxide dismutase (SOD), peroxidase (POD), and catalase (CAT), and the total antioxidant capacity (T-AOC). The results showed that protein content, antioxidant enzyme activity, and T-AOC in T. urticae were significantly induced by heat stress. These results suggest that heat stress induces oxidative stress and that antioxidant enzymes play an important role in reducing oxidative damage in T. urticae. The data of this study will provide a basis for further research on the molecular mechanisms of thermostability and ecological adaptability of T. urticae.